The Difference of Positive or Negative Views on Patients of Soul Disorders Between Students of Faculty of Medicine Hang Tuah University Surabaya Semester 5 with Semester 7 - Pangestika, Fifin Yulia Candra; Wendra, Sadya; Simon, Edward Imanuel (Universitas Hang Tuah, 2019)
Background: Most people in Indonesia still negatively regard mental patients as someone who is dangerous and the disease cannot be cured. This happens because people do not understand well the causes and methods of care for patients with mental disorders. Negative views that exist in the community cause mental patients to get less appropriate and humane treatment in the community even in their own families, such as being installed, ignored, insulted, and alienating family members who experience mental disorders.Objectif: This study aims to determine the differences in positive or negative views of mental patients between students of the Faculty of Medicine, Hang Tuah Surabaya, 5th semester with 7th semester.Methods: The population in this study were students of the Faculty of Medicine, University of Hang Tuah Surabaya in semester 5 with semester 7. with a large sample taken as many as 136 people. The independent variables in this study were positive or negative views about mental patients while the dependent variables in this study were students of semester 5 and semester 7 students. Analysis of the data of this study using Chi Square statistical tests.Results: Obtained results of respondents from semester 5 with a positive outlook that is 38 people (55.9%) and negative views namely 30 people (44.1%), then the results of respondents from 7th semester with a positive outlook that is 53 people (77.9%) and negative view of 15 people (22.1%). Where the total number of all respondents who answered a positive view was 91 people (66.9%) and all respondents who answered negative views were 45 people (33.1%). And based on gender, male respondents who looked positively about mental patients were 51 people (66.2%) and those who viewed negativity were 26 people (33.8%). Whereas female respondents who viewed positively regarding mental patients were 40 people (67.8%) and those who viewed negatively were 19 people (32.2%).Conclusions: The results showed a significant difference regarding the differences in positive or negative views of mental patients between semester 5 students and 7th semester students, as evidenced by the acquisition of the Sig. = 0.006 (<0.05).Keywords: Differences in Positive or Negative Views, Mental Disorders